Changes in caloric consumption, physical activity, body mass index and sleeping pattern during holy month of Ramadan among doctors of a public sector University - Parkash, Arit; Maheswari, Greesh; Shaikh, Shiraz; Anwer, Rabia (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the change in caloric intake, physical activity, body mass index and sleeping pattern during Ramadan among doctors. Method: The longitudinal study was conducted at a public-sector medical university in Karachi from April to May 2020, and comprised healthy doctors of either gender who planned to fast during Ramadan. Data was collected using a multitude of validated structured tools by trained data collectors. Data was analysed using SPSS 20. Results: Of the 193 subjects, 103(53.4%) were females and 90(46.6%) were males. The overall mean age was 30.05±9.4 years. Caloric intake in the month before Ramadan was significantly higher 2288±495kcal/day than during Ramadan 2089±491kcal/day (p<0.001). Calories from proteins decreased and those from fats increased (p<0.001). Metabolic equivalent of task per minute per week increased significantly during Ramadan (p<0.001). Overall sleep per day decreased significantly, and there was an increase in daytime sleep and a decrease in night-time sleep (p<0.05). Body mass index also dropped significantly (p=0.005). Conclusion: Fasting during Ramadan had a positive effect on body mass index and physical activity levels of doctors, while the quality of diet and sleep was affected negatively. Key Words: Caloric consumption, Physical activity, Body mass index, Sleeping pattern, Ramadan.